Competency-Based Curriculum Design and Strategic Career Pathway Integration in Maritime New Cadet Professional Development and Workforce Sustainability - Rosna Yuherlina Siahaan; Larsen Barasa; April Gunawan Malau; Susi Herawati (International Journal of Educational Practice and Policy, 2026)
Maritime workforce sustainability depends on vocational education systems that not only develop technical competencies but strategically align cadet professional development with viable career pathways. Yet current maritime curricula inadequately integrate competency-based design with career development mechanisms. This study investigates how competency-based curriculum design and strategic career pathway integration can strengthen professional development and workforce sustainability among maritime cadets in Indonesian maritime vocational education. A qualitative research design was employed, with semi-structured interviews conducted with 12 maritime industry and career development experts, 18 maritime vocational lecturers, and 15 recent cadet graduates across three maritime polytechnic institutions. Data were analyzed through thematic analysis with open and axial coding, cross-group comparison, and narrative synthesis. Five themes emerged: competency–career misalignment in current curricula, the self-efficacy–career readiness nexus, experiential career immersion deficits, industry-responsive competency framework requirements, and the mentorship–professional identity formation gap. Cross-group analysis demonstrated that experts prioritized workforce pipeline sustainability, lecturers emphasized curricular rigidity, and graduates reported a critical disconnect between certification-based competence and career navigation capacity. The study contributes an integrated competency-career pathway framework that positions career development not as a supplementary guidance function but as a structural curriculum design dimension essential for maritime workforce sustainability. The framework explicitly bridges Social Cognitive Career Theory with competency framework methodology, offering the first theoretically grounded, empirically derived design model for maritime cadet career-integrated education.